The Relationship between Characteristics and Underlying Eye Disorders with Optical Aid Selection and Visual Acuity Status Differences in Children with Low Vision Before and After Optical Aid Selection - Sidohutomo, Andityo; Deneska, Ria Sandy; Loebis, Rozalina (Majalah Oftalmologi Indonesia, 2023)
Background: Low vision is a vision disorder that can have a significant impact on a person's independence, especially in children. According to WHO data from 2019, 246 million people suffer from low vision. Ophthalmologists must prioritize low-vision services such as refractive correction and low-vision assessment. This study aims to learn more about the relationship between characteristics and underlying eye disorders with optical aid selection, as well as differences in visual acuity status in children with low vision before and after optical aid selection. Methods: This study was an analytic observational retrospective cohort using medical records of children with low vision in RSUD Dr. Soetomo Surabaya. This study analyzed the relationship between characteristics (gender, age, education level, intervention history) and underlying eye disorders with optical aid selection using the Chi-Square test, while visual acuity status differences before and after optical aid selection were analyzed using the Wilcoxon test. Results: There were no relationships between characteristics (gender, age, education level, intervention history) and underlying eye disorders with optical aid selection (p > 0.05). There were differences in visual acuity status before and after optical aid selection (p < 0.05) with a minimum decrease of 0.1 logMAR which means an increase in visual acuity in all 72 samples of children with low vision after optical aid selection. Conclusion: These data provide new evidence of essential links between visual acuity status before and after optical aid selection. However, characteristics (gender, age, education level, intervention history) and underlying eye disorders were not associated with optical aid selection.